Role of genetic variations of chitinase 3-like 1 in bronchial asthmatic patients - Kazuyuki Abe; Yutaka Nakamura; Kohei Yamauchi; Makoto Maemondo (Clinical and Molecular Allergy, 2018)
Abstract Background Single nucleotide polymorphisms (SNPs) in chitinase 3-like 1 (CHI3L1) are associated with bronchial severity and pulmonary function. CHI3L1 proteins are involved in both innate and adaptive immune responses; however, to date, the correlation of these SNPs and their age of onset of bronchial asthma has not been demonstrated. Methods To address the role of these genetic variations, 390 patients with well-controlled bronchial asthma and living in Japan were recruited, genotyped, and had a pulmonary function test performed on them in this study. To analyze the concentration levels of CHI3L1 protein, bronchial lavage fluids were examined. Results Forced expiratory volume in one second, %predicted (%FEV1), was significantly decreased in homozygotes of rs1214194 compared to heterozygotes and wild type. The age of onset of adult bronchial asthma was significantly younger in GG homozygotes of rs4950928 and AA homozygotes of rs1214194 than in the other two genotypes. The concentration of CHI3L1 protein in bronchial lavage fluid increased in both homozygotes of rs4950928 and rs1214194. Conclusions Our study demonstrated that the homozygotes of rs4950928 and rs1214194 of CHI3L1 might predict an early onset of bronchial asthma and have the propensity to promote airway remodeling. Trial registration JMA-IIA00045 remodeling-ICS